2008
DOI: 10.1590/s1807-59322008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Trabeculectomy with Mitomycin C for Childhood Glaucoma: A Study of Results with Long-Term Follow-Up

Abstract: OBJECTIVETo evaluate the safety and effectiveness of trabeculectomy with mitomycin C in the management of childhood glaucoma.INTRODUCTIONThe use of antifibrotic agents enhances the success of trabeculectomy performed in both adults and children.METHODSA retrospective chart review (1991–2001) of 114 patients (114 eyes) from 0–14 years of age with congenital or developmental glaucoma. These patients underwent trabeculectomy with mitomycin but had not been previously treated with any antifibrotic agent.RESULTSThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…The results reported by Giampani et al . [21] showed that trabeculectomy with mitomycin C was safe and effective for the treatment of congenital glaucoma, and that the frequency of bleb-related endophthalmitis was no higher than that described in adults. In some studies in developed countries, postoperative endophthalmitis was the most common form, and Benz et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results reported by Giampani et al . [21] showed that trabeculectomy with mitomycin C was safe and effective for the treatment of congenital glaucoma, and that the frequency of bleb-related endophthalmitis was no higher than that described in adults. In some studies in developed countries, postoperative endophthalmitis was the most common form, and Benz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported bleb leaks as the most common complication of trabeculectomy with mitomycin 19,20,22,25,27 and as a predisposing factor for blebitis and endophthalmitis. 17,20,21,29,30 Soltau et al 31 reported a likelihood of late-onset bleb leakage in bleb-related infection 25.8 times that of a noninfected eye for having a late-onset bleb leak in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey in 2007, Yalvac et al8 reported that the success rates of trabeculotomy after 12, 24, and 36 months were 92%, 82%, and 74%, respectively. In 2008, a study in Brazil reported trabeculectomy success rates at 24, 36, 48, and 60 months of 90.2%, 78.7%, 60.7%, and 50.8%, respectively 5. In the U.S., Mendicino et al25 compared 360° trabeculotomy and goniotomy and concluded that 360° trabeculotomy is a highly effective procedure that results in excellent pressure control and better vision than is reported in the literature for standard angle procedures 25, 31.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Brazil that evaluated 3,210 visually impaired children, congenital glaucoma was responsible for 10.8% of the visual impairments 3. The incidence of congenital glaucoma varied between counties, ranging from 1/10,000-1/30,200 4,5. Since at least 50% of eyes presenting with primary congenital glaucoma (PCG) at birth will become legally blind, patients with PCG require not only prompt treatment but also follow-up examinations and care throughout their lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation